Obstacles to the diffusion of adaptation in the Rhein-Neckar region in Germany - Schmidt, Nicole; Wagner, Madeleine (Regional environmental change, 2023)
Because the impacts of climate change are felt at the local level, we assess adaptation diffusion mechanisms (i.e., learning, competition, and emulation) among smaller big cities and medium-sized towns. Since the diffusion of adaptation has immediate spatial implications, we argue that local conditions play an important role in the diffusion process. The densely populated Rhein-Neckar Metropolitan Region in Germany is an ideal case for studying diffusion mechanisms with regard to adaptation. Using a rich data set of 28 interviews, we unpack the views of local actors such as mayors, city council politicians, city administration representatives, and representatives from regional agencies and identify factors influencing the diffusion of adaptation. We find limited or compromised diffusion due to insufficient knowledge about adaptation, competition between municipalities, and cooperation with cities outside the region. In addition, we find some (albeit limited) political will for adaptation. While some of the interviewed politicians considered making long-term investments in adaptation, most highlighted competing local issues and viewed adaptation with caution, illustrating adaptation’s lack of salience and social legitimacy. Indeed, one crucial finding was that housing and mobility are more important to a wide range of politicians and bureaucrats alike. By examining diffusion mechanisms at the subnational level, we combine theoretical perspectives from political science and geography to show how local decision-makers—in particular, politicians—influence the diffusion mechanisms of adaptation.
Gesehen am 19.06.2023